Research on the AVC Testing Platform for the Regional Grid based on Real-Time Digital Simulator (RTDS) - Lin Xu; Yang Han (Institute of Advanced Engineering and Science, 2013)
The automatic voltage control (AVC) relay provides real-time automatic control for the on-load transformer tap changer (OLTC), which is widely used for power system voltage monitoring and control purposes throughout the world. However, there are no uniform testing standards for the AVC system, and the lack of on-site inspection means has stimulated the introduction of the real-time digital simulator (RTDS)-based testing platform. This paper introduces the testing platform of the AVC controller based on the RTDS. The circuit model of the regional power grid is established, and the OLTC and the reactive power compensation devices are also incorporated. The intermediate data conversion device is utilized for bi-directional data exchange of the remote meter and control signals between the RTDS and the AVC system. The principle of the AVC voltage regulation and the RTDS-based AVC testing platform are introduced, followed by the data flow of the OLTC and capacitor/inductor banks, which formulates the foundation for closed-loop testing of the AVC control system for the electric power system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1677